Magnonics Along the Wall in Bimeron Chain Domain Walls - Allende-Prieto, S; Saavedra-Díaz, E (American Physical Society, 2025)
We demonstrate that domain walls built from bimeron chains in two-dimensional systems constitute a spontaneously assembled medium that holds magnonic excitations along its direction. We prove that such magnons are topological, leading to protected edge states. We also verify the stability of the domain walls and the resilience of edge modes against disorder. Analytical calculations and micromagnetic simulations support our findings. The robustness of these edge modes holds promise for potential applications in the design of nanoscale magnonic devices for information storage and transport. © 2025 American Physical Society.